Management of thymoma‐associated pure red cell aplasia: A novel use of blood substitute HBOC‐201 in a Jehovah's Witness. Issue 2 (26th December 2019) - Rubinstein, Maria M.; Goss, Cheryl; Avecilla, Scott T.; Dubé, Gregory P.; Riely, Gregory J.; Mones, Jodi V.
Abstract: Pure red cell aplasia (PRCA) is a rare paraneoplastic syndrome occasionally associated with thymomas. Here, we report on the first ever use of a bovine hemoglobin‐based oxygen carrier, HBOC‐201 (HbO2 Therapeutics LLC; Hemopure ®, Waltham, MA) for the supportive management of pure red cell aplasia in a Jehovah Witness patient. Abstract : Pure red cell aplasia (PRCA) is a rare paraneoplastic syndrome occasionally associated with thymomas. Here, we report on the first ever use of a bovine hemoglobin‐based oxygen carrier, HBOC‐201 (HbO2 Therapeutics LLC; Hemopure ®, Waltham, MA) for the supportive management of pure red cell aplasia in a Jehovah Witness patient.